Client Racial Composition in First-Episode Psychosis Programs Compared With Compositions in Program Service Areas. - Daley, Tamara C.; George, Preethy; Goldman, Howard H.; Krenzke, Tom; Zhu, Xiaoshu; Ren, Weijia; Giangrande, Michael; Ghose, Shoma; Rosenblatt, Abram (Psychiatric Services, 2022)
Objective: The authors examined the extent to which clients served by first-episode psychosis programs reflected the racial composition of the surrounding service area and, to the extent that they did not, explored possible explanatory factors.Methods: As part of a national study of coordinated specialty care (CSC) sites in the United States, 35 programs documented race for 772 clients. Programs identified a geographic service area for their clients. Using Census data, the authors identified the proportion of clients in this service area who were Black and then examined the extent of disproportionality, calculated as a risk ratio and as a relative difference in racial composition between CSC programs and their service areas.Results: Overall, 71% of CSC programs had a disproportionately greater proportion of Black clients than Black residents within the service area. This disproportionality was still evident after conducting sensitivity analyses that included adjusting for sampling error in the service area population estimates; however, smaller study sites displayed greater fluctuations in disproportionality in the sensitivity analyses.Conclusions: Using data from diverse CSC programs, the authors illustrate that the odds of Blacks receiving services through a CSC program are much higher than would be expected on the basis of the population living in the area being served by the program. Multiple reasons may explain this finding, but in the absence of clear explanatory factors, this result may be ripe for discussion and further investigation.